Fenomena Product Line Extention: Efek Kepercayaan Dalam Memediasi Ulasan Konsumen dan Selebriti Endorser Terhadap Minat Beli Pada - Pandowo, Aditya; Grace Christien Sumakul (Eqien - Jurnal Ekonomi dan Bisnis, 2025)
The research purposive is to examine the determinants of purchase intention derived from customer reviews and celebrity endorsers and explore the role of trust as a mediator. The current investigation is designed in a quantitative approach with purposive sampling with criteria of having bought and interested in buying different products with the same brand and at least 102 respondents were involved in this study. The research found that customer reviews affect trust and purchase intention. Meanwhile, celebrity endorsers affect trust, but not significantly toward purchase intention. In the meantime, trust affects purchase intention directly. In intervening testing, trust was shown to mediate the relationship of customer reviews with purchase intention partially, and the relationship of celebrity endorsers with purchase intention as fully mediation. The current research contributes to providing additional marketing literacy, especially those related to antecedents of purchase intention, and as a foothold for business entities in taking marketing strategies that aim to foster customer purchase intention. In addition to product and brand limitations, current research is also less comprehensive because it only includes customer reviews, celebrity endorsers, and trust as determinants of purchase intention